Pemanfaatan Media Digital dalam Pembelajaran Pendidikan Agama Islam dan Literasi Digital Siswa: Kajian Literatur - Hamka Al Hakim; Muhammad Joko Susilo (Al-Mudarris, 2026)
Digital transformation in Islamic Religious Education (PAI) faces an epistemological challenge: bridging the gap between technical proficiency and the internalisation of Tauhid (monotheism) and moral responsibility (Akhlak). This study analyses the utilization of digital media and student literacy profiles through a qualitative library research approach, synthesised using Miles, Huberman, and Saldaña’s interactive model. The findings reveal that current digital integration remains predominantly instrumental, focusing on interactivity while neglecting the normative dimensions of Islamic digital ethics. Consequently, students exhibit high technical skills but fragile critical reasoning, leading to the erosion of scientific authority (sanad) and susceptibility to religious misinformation. This article contributes theoretically by proposing a pedagogical framework where digital literacy is anchored in the principle of Tabayyun (verification). Practically, the study implies a managerial imperative for madrasah administrators to reconstruct the educational ecosystem. This involves formulating curriculum policies that explicitly integrate digital ethics and supervising teachers to function as authoritative curators of knowledge. These measures are vital to ensuring that digital adoption aligns with the ultimate goal of Islamic education: cultivating students who are technically competent yet spiritually and morally grounded.